Doxycycline for Alzheimer’s Disease: Fighting β-Amyloid Oligomers and Neuroinflammation - Balducci, Claudia; Forloni, Gianluigi (Frontiers in Pharmacology, 2019)
Alzheimer’s disease (AD) is the most widespread form of dementia, affecting about 45 million people worldwide. Although the β-amyloid peptide (Aβ) remains the most acknowledged culprit of AD, the multiple failures of Aβ-centric therapies call for alternative therapeutic approaches. Conceivably, the complexity of the AD neuropathological scenario cannot be solved with single-target therapies, so multiple-target approaches are needed. Core targets of AD to date are soluble oligomeric Aβ species and neuroinflammation, in an intimate detrimental dialogue. Aβ oligomers, the most neurotoxic species, appear to induce synaptic and cognitive dysfunction through the activation of glial cells. Anti-inflammatory drugs can prevent the action of Aβ oligomers. Neuroinflammation is a chronic event whose perpetuation leads to the continuous release of pro-inflammatory cytokines, promoting neuronal cell death and gross brain atrophy. Among the possible multi-target therapeutic alternatives, this review highlights the antibiotic tetracyclines, which besides antimicrobial activity, also have pleiotropic action against amyloidosis, neuroinflammation and oxidative stress. A particular focus will be on Doxycycline (Doxy), a second-generation tetracycline that crosses the blood brain barrier more easily and has a safer clinical profile. Doxy emerged as a promising preventive strategy in prion diseases and gave compelling pre-clinical results in mouse models of AD against Aβ oligomers and neuroinflammation. This strongly supports its therapeutic potential and calls for deciphering its exact mechanisms of action so as to maximize its effects in the clinic.